Strategi Pengembangan Bisnis dengan Metode Product Life Cycle (PLC) dan Boston Consulting Group (BCG) Matriks - Lisa Sulistyawati; Maya Arieska Dinda Septiani (LPPM Institut Nasional Laa Roiba Bogor, 2022)
Micro, Small and Medium Enterprises (UMKM) are an important sector because UMKM are activities carried out by the government to help the economy of people who want to open small businesses in the traditional and modern sectors. Batik Very Jelita Batam is one of the many batik cloth entrepreneurs in Batam City and is currently facing tough business competition. Therefore, Batik Very Jelita Batam needs to know the stages and position of its current business in order to get a new business strategy and increase sales by using the Product Life Cycle (PLC) and Boston Consulting Group (BCG) Matrix methods so as to produce improvements to the business strategy that has been implemented in order to reach the right stage and position of the business. he method used in this research is descriptive which aims to analyze, understand, and explain the data obtained by the researcher into descriptive conclusions. Data collection techniques were carried out through observation and documentation. The types and sources of this research data are secondary data, where data sources that do not directly provide data results to researchers or data collectors, for example through literature studies or documentation that has been processed by the company. The results of the study show that the Product Life Cycle (PLC) curve shows that the business is in a growth stage, namely the stage where the product introduced is already known and acceptable to consumers. Meanwhile, on the Boston Consulting Group (BCG) Matrix curve, it is in a question mark position, namely a relatively low market share position, but competitive and a fast-growing industry, at this stage the cash needs are high and cash income is low. From the results of calculations and curves using this method, improvement of business strategy becomes input for the owner and management of Batik Very Jelita Batam. Keywords: